A review on microgrids for the distributed integration of renewable hydrogen production with the power system - Nascimento Silva, Gabriel Lucas; Danielly Norberto Araújo; Danilo Pinchemel Cardoso Filho; André Gama; Heloisa Althoff (Latin American Journal of Energy Research, 2024)
Technological advancements in the power system, coupled with the electrification of various sectors, decarbonization policies, and solutions for conflicting demands in the electrical sector, have driven the integration of new distributed resources, increasing the system’s complexity. In this context, microgrids stand out as a new power system operational paradigm, along with hydrogen production via clean energy-based electrolysis as a promising source of alternative and renewable resources. However, there are few studies that specifically explore the potential of microgrids as a vector for large-scale distributed production of renewable hydrogen. This article provides a comprehensive review of the different power system dimensions, systematically assessing this potential. An updated overview of the most widely accepted definitions of microgrids is presented, highlighting applicable hydrogen technologies, whether to be used as a primary source, storage method, fuel, or main product. Additionally, examples of studies and projects that contribute to the technical and economic feasibility of microgrids as a means of integrating hydrogen production into the power system are discussed.